Kebijakan Pendidikan Pasca Orde Baru - Husin, Husin; Su’adi, Su’adi; Elwidah, Minah; Sudur, Sudur (Innovative: Journal Of Social Science Research, 2024)
Islamic education in the post-New Order era has experienced developments both quantitatively and in terms of quality of implementation. The policies of the post-New Order era in Islamic education, for example: the government enforced Islamic religious education to be taught in elementary schools to higher education, madrasah and pesantren institutions began to be recognized, facilities were provided and so on. Government policies during the post-New Order era, although they provided a breath of fresh air for the development of Islamic education, stakeholders had to struggle and work hard to convince the government that the existence of Islamic education would continue to be recognized and have the same position as other education nationally.